THE EFFECT PROBLEM BASED LEARNING ASSISTED BY QUESTION CARDS ON CRITICAL THINGKING SKILLS ON ADDITIVE AND ADDICTIVE SUBSTANCES FOR VIII GRADE STUDENTS OF SMPN 38 PADANG - Safitri, Violetta; lestari, Tuti (Universe, 2024)
Education is an activity carried out by teachers and students to improve knowledge, skills, character and problem solving in life. Critical thinking skills possessed by learners can be used in solving a problem that may be encountered in everyday life or natural phenomena that arise. The use of effective and interesting learning models can affect the level of critical thinking skills in students. This study aims to determine the effect of problem-based learning model assisted by question cards on additive and addictive substances on critical thinking skills of students in class VIII SMP N 38 Padang. The type of research used is quasy experiment with non-equivalent control group design. The experimental class used a problem-based learning model, while the control class used a conventional learning model with lecture and question and answer methods. The results of data analysis showed hypothesis testing based on pretest data, namely Tcount -0.49 < Ttabel 2.06 and postest Tcount 8.22 > Ttabel 2.06. N-gain data of experimental class 0.72 (high) and control class 0.24 (medium). The conclusion of this study is that there is an effect of problem-based learning model assisted by question cards on the material of additives and addictive substances on the critical thinking skills of students in class VIII SMP 38 N Padang.